Determinants of going concern audit opinion: An empirical study in Indonesia - Arief Bahtiar; Neni Meidawati; Primanita Setyono; Novika Rahma Putri; Rizki Hamdani (Jurnal Akuntansi dan Auditing Indonesia, 2021)
This study aims to analyze and provide empirical evidence about the effect of liquidity, leverage, profitability, audit tenure, audit lag, and audit quality on the going concern audit opinion on manufacturing companies listed on the Indonesia Stock Exchange between 2015 and 2019. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) with the total of 176 companies. The determination of the sample uses purposive sampling which leave 20 manufacturing companies that meet the criteria. In this research, the data analysis method used is the logistic regression analysis method because there are dummy variables on the dependent and independent variables. The results of this study indicate that liquidity and profitability have a negative effect, and audit lag has a positive effect on the acceptance of going concern audit opinion. While the variable leverage, audit tenure, and audit quality does not affect the going concern audit opinion.